2019
DOI: 10.1111/rode.12617
|View full text |Cite
|
Sign up to set email alerts
|

Temporary and permanent migrant selection: Theory and evidence of ability‐search cost dynamics

Abstract: We integrate two workhorses of the labor literature, the Roy and search models, to illustrate the implications of migration duration-specifically, whether it is temporary or permanent-for patterns of selection. Consistent with our stylized model, we show that temporary migrants are intermediately selected on education, with weaker selection on cognitive ability. In contrast, permanent migration is associated with strong positive selection on both education and ability, as it involves finer employee-employer ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 67 publications
1
5
0
Order By: Relevance
“…This may be related to capabilities and resources needed for migration (De Haas, 2021), apart from the possibility of reverse causality. However, wealth is negatively associated with temporary migration, meaning that temporary migration is more commonly observed among the poor, as also found in the existing studies (Chen et al, 2019;Keshri & Bhagat, 2013). Finally, agriculture-dependent households, either through own farming or labor sales, are more likely to migrate temporarily during lean periods.…”
Section: Factors Explaining Migrationsupporting
confidence: 58%
See 4 more Smart Citations
“…This may be related to capabilities and resources needed for migration (De Haas, 2021), apart from the possibility of reverse causality. However, wealth is negatively associated with temporary migration, meaning that temporary migration is more commonly observed among the poor, as also found in the existing studies (Chen et al, 2019;Keshri & Bhagat, 2013). Finally, agriculture-dependent households, either through own farming or labor sales, are more likely to migrate temporarily during lean periods.…”
Section: Factors Explaining Migrationsupporting
confidence: 58%
“…Longer-term migrason is not only longer but ouen also involving higher-paying jobs; hence the larger income effects are unsurprising. However, longer-term migrason is typically also more demanding than temporary migrason in terms of financial and emosonal costs and requirements (Coffey et al, 2014;Chen et al, 2019;Lagakos et al, 2023). We have shown that poorer households with family constraints are less likely to engage in longer-term migrason.…”
Section: Migration Effects On Dietary Quality and Incomementioning
confidence: 77%
See 3 more Smart Citations